2015
DOI: 10.1002/2015gl063269
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of sprite streamers in varying air density

Abstract: Similarity laws for streamer discharges, which state that the properties of streamers such as streamer radius, electric field, and electron density should respectively scale as N−1, N1, and N2 in different but uniform air densities N, are important relations that have provided a general understanding of the mesospheric sprite discharges based on existing knowledge of streamers in laboratory conditions. Recent modeling studies, however, show that the properties of sprite streamers in varying air density do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Wu et al () attributed their observed decreasing NIL speed with increasing height (their flashes were all initiated below 12 km) to the drop in the breakdown electric field with increasing height, which meant that the ambient electric field for flash propagation tends to be smaller at a higher position than the lower position. Previous studies showed that streamer properties are affected by air density, the electric field, and their physical dimensions (Liu & Pasko, ; Qin & Pasko, , ); the streamer electron mobility varies positively with electric field and inversely with air density. Therefore, a decreasing electric field with height reduces NIL speed, whereas the decreasing air density with height accelerates the NIL.…”
Section: Discussionmentioning
confidence: 97%
“…Wu et al () attributed their observed decreasing NIL speed with increasing height (their flashes were all initiated below 12 km) to the drop in the breakdown electric field with increasing height, which meant that the ambient electric field for flash propagation tends to be smaller at a higher position than the lower position. Previous studies showed that streamer properties are affected by air density, the electric field, and their physical dimensions (Liu & Pasko, ; Qin & Pasko, , ); the streamer electron mobility varies positively with electric field and inversely with air density. Therefore, a decreasing electric field with height reduces NIL speed, whereas the decreasing air density with height accelerates the NIL.…”
Section: Discussionmentioning
confidence: 97%
“…The local electric field needed for the initial virgin breakdown of a flash decreases with increasing altitude (Marshall et al, ), which indicates the ambient electric field supporting the propagation of IL also decreases with increasing altitude. The electron mobility ahead of the IL tip varies positively with electric field (Liu & Pasko, ; Qin & Pasko, , ); therefore, the speed of the IL tends to decline as their initiation altitudes increase. Edens et al () proposed that the low air pressure and density could cause a longer mean free path of free electrons and larger streamer zones ahead of the leader tip; therefore, the step of the IL propagating at a high level tended to be longer than that at a low level.…”
Section: Discussionmentioning
confidence: 99%
“…However, to make our results independent of the assumptions required to build such models, here we opt for a microscopic, advection‐reaction model. This type of model underlies most theoretical studies of sprites (for recent examples, see Luque and Ebert [], Qin and Pasko [], Liu et al [], and Neubert et al []). Their drawback is that they are computationally expensive so they are usually limited to a cylindrically symmetrical configuration, and therefore, they can follow a sprite's evolution only as long as this symmetry is preserved, which is typically a few milliseconds.…”
Section: Modelingmentioning
confidence: 98%